KARAKTERISASI SIFAT OPTIK C-DOTS DARI KULIT LUAR SINGKONG MENGGUNAKAN TEKNIK MICROWAVE - Putro, Permono Adi; Roza, Liszulfah; -, Isnaeni (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Carbon dots (C-dots) are a new type of phosphorescent nanoparticles that can be easily synthesized from natural sources or raw materials. The outer shell of cassava is the second waste obtained from cassava skin waste which is less attention to be utilized. Synthesis of C-dots from the outer shell of dried cassava has been successfully carried out with Microwave techniques. Synthesis of C-dots was carried out using water as a solvent with a variation of the concentration of precursor solutions to the microwave duration. Microwave duration causes changes in the structure and optical properties of C-dots. C-dots are characterized to study the optical properties of the UV-Vis absorbance spectrum and emission intensity in the form of emissions. The observed optical properties aim to determine the C-dots energy transition, such as surface and core energy. The core energy level becomes dominant in the transition Ï€â†’Ï€* compared to the transition of nâ†’Ï€* in surface energy when the C-dots concentration increases so that energy shifts. This phenomenon is known from the top of the broad C-dots emission spectrum and shifts to longer wavelengths. In addition, we suspect that the difference in C-dots emissions is caused by the molecular density and content of the preparation based on the concentration of precursor solutions and the length of microwave time.